Organic electro-optics and photonics : molecules, polymers, and crystals - Dalton, Larry R. (Cambridge University Press, 2015)
This definitive guide to modern organic electro-optic and photonic technologies provides critical insight into recent advances in organic electro-optic materials, from the underlying quantum and statistical concepts through to the practical application of materials in modern devices and systems.- Introduces theoretical and experimental methods for improving organic electro-optic and photonic technologies- Reviews the central concepts of nonlinear optics, focusing on multi-scale theoretical methods- Provides clear insight into the structure and function relationships critical to optimizing the performance of devices based on organic electro-optic materials. Serving as a primer for the systematic nano-engineering of soft matter materials, this is an invaluable resource for those involved in the development of modern telecommunication, computing, and sensing technologies depending on electro-optic technology. It is also an indispensable work of reference for academic researchers and graduate students in the fields of chemistry, physics, electrical engineering, materials science and engineering, and chemical engineering.